(untitled) (Journal of Rangpur Medical College, 2025)
Introduction: The SARS-CoV-2 pandemic has significantly impact on global health, with clinical presentations ranging from asymptomatic to severe, leading to complications like pneumonia, ARDS, sepsis, organ failure, and COVID-19-related deaths. Olfactory dysfunction (OD) is a prevalent symptom of COVID-19, affecting 47.9% to 70% of patients and contributing to a significant rise in global OD cases Objective: This study was aimed to evaluate the prevalence and characteristics of smell abnormalities in field-level healthcare providers in Bangladesh following SARS-CoV-2 infection. Methods: A cross-sectional descriptive was conducted at Department of ENT and Head-Neck Surgery, Ad-din Sakina women’s medical college, Jashore, Bangladesh, from January , 2022 to December, 2022 on 100 front-line health care works of various health care institutes of Bangladesh to investigate post-SARS CoV-2 smell function using integrated structured interviews and standardized olfactory test. Results: Among 100 patients, 81% demonstrated normal olfactory function. 14% developed hyposmia, 3% anosmia and one patient developed cacosmia and parosmia each. Conclusion: The study highlights the significant impact of SARS-CoV-2 on olfactory function among frontline healthcare workers in Bangladesh. The findings underscore the need for continued research and awareness regarding olfactory dysfunction, particularly among those at the frontline of healthcare. J Rang Med Col. 2025 Sep;10(2): 146-151